Examining the Impact of Organizational and Individual Factors on Lecturer Performance in Tangerang Universities - Rika Nurhidayah; Horas Djulius; Atty Tri Juniarty (International Journal of Economics, Business and Innovation Research, 2026)
Lecturer performance is a central determinant of academic quality in Indonesian higher education, yet empirical evidence on the relative contributions of organizational and individual factors remains limited in the Tangerang context. Objective: This study investigates the simultaneous and partial effects of organizational culture, transformational leadership, job satisfaction, and work motivation on lecturer performance at private universities in Tangerang City and Tangerang Regency, Indonesia. A quantitative survey design was employed. Data were collected from 214 permanent lecturers across six accredited private universities through stratified random sampling. Structural Equation Modeling–Partial Least Squares (SEM PLS) was used for data analysis. Validity was assessed via convergent and discriminant criteria; reliability was confirmed through composite reliability and Cronbach's alpha. All four predictors demonstrated significant positive effects on lecturer performance. Work motivation exhibited the strongest direct effect, followed by transformational leadership, organizational culture, and job satisfaction. Enhancing lecturer performance in Tangerang universities requires an integrated approach addressing both organizational level interventions (leadership development, cultural reinforcement) and individual level support (motivation strategies and satisfaction mechanisms). Implications for higher education policy and institutional management are discussed